Sustainable Tourism and Its Relationship with Green Hospitality - Nandini Bharill; Namita Soni (AG Volumes, 2026)
The rapid evolution of global tourism has underscored the urgent need for sustainable practices, especially in the hospitality sector which significantly impacts environmental and socio-economic systems. Sustainable tourism, emphasizing responsible resource use, cultural integrity, and community development, has found strong synergy with green hospitality—a domain committed to eco-conscious hotel and lodging practices. This research explores the dynamic relationship between sustainable tourism and green hospitality by reviewing recent empirical evidence and theoretical advancements from 15 high-impact studies published between 2024 and 2026. The study synthesizes findings across micro (firm-level), meso (destination-level), and macro (policy-level) perspectives. It highlights how green human resource management (GHRM), eco-certifications, green innovation, and sustainable destination policies collaboratively enhance tourist satisfaction, operational efficiency, brand reputation, and environmental performance. Moreover, the paper uncovers how behavioral interventions—like green menu design, energy efficiency campaigns, and local sourcing—play a pivotal role in influencing tourist behavior and reducing ecological footprints. By applying integrative frameworks such as the Resource-Based View (RBV) and Institutional Theory, the study provides a conceptual model linking green practices to long-term competitive advantage in hospitality. Findings suggest that while green initiatives contribute positively to sustainable tourism development, challenges persist in implementation, scalability, and stakeholder alignment. The research concludes with actionable insights for hotel managers, policymakers, and destination planners to bridge the gap between sustainability goals and practical execution. It also calls for future research using multilevel and longitudinal methodologies to better assess the long-term impact of green hospitality on sustainable tourism systems.